Characteristics of strong earthquake preparation in main-seismic type and multi-seismic type earthquake segments in the North China tectonic region - Zhu, Hongbin; Hu, Leyin; Chen, Yuxuan; Li, Hong (Frontiers in Earth Science, 2024)
The North China Tectonic Zone (NCTZ) is the most seismically active area in eastern China, where a large number of strong earthquakes, especially M8 or so, had occurred. In order to study the risk of future strong earthquakes in the NCTZ, we study tectonic features of strong earthquakes and the time series features of Ms ≥ 5 earthquakes since the year 1484 (MT). The results show that the 14 seismic segments of faults are classified into Main-seismic types and multi-seismic types. The characteristics of the main seismic segment include: NNE dextral strike-slip faults, only one prominent around M8 main shock has occurred since the year 1484, most of the deep and large faults cutting the Moho surface below the main earthquakes with high angles, the flower structures of tectonics. The characteristics of multi-seismic type include: NWW left-lateral strike-slip faults, NEE oriented tensional faults, convergence areas of several sets of faults since the year 1484, and the magnitude of most of them was not greater than M7.0. Finally, we analyze the strong-earthquake-generating characteristics of the similar seismic segments and discuss their strong-earthquake-generating patterns based on the relationship between the rupture zone and the main compressive stress field.